Concentrating Solar Power Technologies: A Bibliometric Study of Past, Present and Future Trends in Concentrating Solar Power Research - Calderón, Alejandro; Barreneche, Camila; Prieto, Cristina; Segarra, Mercè; Fernández, A. Inés (Frontiers in Mechanical Engineering, 2021)
Bibliometric analysis is a key study in order to elucidate the relevance of a research field. This study will point out the main evolution of a research performed in a topic considering the significance of each sub-topic. This study aims to perform a bibliometric analysis in concentrating solar power (CSP) technology. CSP had a first commercial wave between 1984 and 1995. Between 1995 and 2005 there was a period of commercial inactivity. Nevertheless, since 2005 CSP commercial implementation has been accelerating. This topic accounts almost 6,300 publications on relevant journals and conference proceedings. Regional analysis showed that China is becoming the most relevant country for CSP research. European Union still leads the development and will continue that way at least in the short term. Authors’ keyword evolution analysis has been useful as an indirect measure of technological maturity. It was found that conference proceedings have an important effect in the overall CSP publications and need to be consider when working within this field. However, the journal publications use to have more impact since they are more frequently cited. Funding analysis had shown a direct relationship between funding and research output. Finally, it was concluded that inside CSP field, parabolic trough has shown to have great relevance in the research output.